Identifikasi Serangga Hama pada Tanaman Cabai Rawit (Capsicum frutescens L.) pada Fase Generatif di Lahan Tani Air Terjun Pinang Seribu Kelurahan Sempaja Utara Samarinda - Widiyanti, Tanti; Lumowa, Sonja Verra Tinneke; Masitah, Masitah; Purwati, Sri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Cayenne pepper (Capsicum frutescens L.) is a horticultural commodity with high economic value that is widely consumed by the Indonesian people, but is susceptible to various types of pests, especially in the generative phase. This study aims to identify the type and dominance of insect pests that attack cayenne pepper plants in the generative phase in the farmland of Thousand Pinang Waterfall, North Sempaja Village, Samarinda. The research methods used include direct observation and insect collection using several types of traps (insect nets, light traps, and pitfall traps). Identification is carried out down to the family level with the help of a keybook of determination and morphological character of insects. The results of the study showed the existence of several insect pest families such as Tephritidae (fruit flies), Thripidae (thrips), Aphididae (aphids), and Bemisiidae (whiteflies) that were dominant during the generative phase of the plant. So it can be concluded that cayenne pepper plants in the generative phase in the farmland of the Thousand Pinang Waterfall, Samarinda, are vulnerable to being attacked by various types of insect pests. This is important to support a more precise and effective pest control strategy in the critical phase of the growth of cayenne pepper plants.